2017
DOI: 10.3168/jds.2016-11822
|View full text |Cite
|
Sign up to set email alerts
|

Water use on nonirrigated pasture-based dairy farms: Combining detailed monitoring and modeling to set benchmarks

Abstract: Water use in intensively managed, confinement dairy systems has been widely studied, but few reports exist regarding water use on pasture-based dairy farms. The objective of this study was to quantify the seasonal pattern of water use to develop a prediction model of water use for pasture-based dairy farms. Stock drinking, milking parlor, and total water use was measured on 35 pasture-based, seasonal calving dairy farms in New Zealand over 2 yr. Average stock drinking water was 60 L/cow per day, with peak use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 27 publications
5
38
1
Order By: Relevance
“…In 2006, 78% of New Zealand's extracted water was used for irrigation, 3% for livestock drinking, with the remainder for public and industry use (New Zealand Parliament 2011). An estimated 26% of stock drinking water is lost through leaks, which, in turn, can damage pasture and increase energy use for pumping water (Higham et al 2017). Electricity use in New Zealand produces average emissions in CO 2 equivalents (CO 2 e), of approximately 150 g CO 2 e/kWh (unpublished data S. Falconer and S. Ledgard 2020), compared to 2,990 g CO 2 e/L diesel and 2,760 g CO 2 e/L petrol (Ledgard et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In 2006, 78% of New Zealand's extracted water was used for irrigation, 3% for livestock drinking, with the remainder for public and industry use (New Zealand Parliament 2011). An estimated 26% of stock drinking water is lost through leaks, which, in turn, can damage pasture and increase energy use for pumping water (Higham et al 2017). Electricity use in New Zealand produces average emissions in CO 2 equivalents (CO 2 e), of approximately 150 g CO 2 e/kWh (unpublished data S. Falconer and S. Ledgard 2020), compared to 2,990 g CO 2 e/L diesel and 2,760 g CO 2 e/L petrol (Ledgard et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Across four AMS brands, Brøgger Rasmussen and Pedersen [27] calculated an average parlor water consumption of 0.4 L w kg −1 milk, equal to that consumed by the traditional milking systems. Higham et al [28] also monitored and analyzed 35 pasture-based dairy farms (herd size range = 160-1150 cows) in New Zealand over a period of two years (June 2013 to May 2015) and calculated a parlor water usage value of 3.9 L w kg −1 milk. In Germany, Krauß et al [29] analyzed the cleaning water use within a dairy barn (herd size = 176 cows), autonomously monitoring hourly water usage across two milking systems (a herringbone and an AMS) over 806 days.…”
Section: Parlor Water Consumptionmentioning
confidence: 99%
“…This concurred with findings reported by Robinson et al [33] in which 17 Ontario dairy farms were analyzed and found to consume greater volumes of water during the summer months than in winter (p < 0.05). In New Zealand, Higham et al [28] utilized 35 pasture-based dairy farms to calculate an average drinking-water consumption of 60 L w cow −1 day −1 , although this figure was corrected to 36 L w cow −1 day −1 when adjusted for leakage (mean milk production of 12.8 kg cow −1 day −1 ). Contradictory to Brugger and Dorsey [26] and Robinson et al [33], Higham et al [28] reported reduced total water usage during the summer months.…”
Section: Free Water Intakementioning
confidence: 99%
See 2 more Smart Citations